200 Benefits and Challenges of Human-Centered Design: Perspectives from Research Teams. (April 2022) - Norman, Marie; Hamm, Megan E.; Schenker, Yael; Mayowski, Colleen A.; Hierholzer, William; Rubio, Doris M.; Reis, Steven E.
Abstract : OBJECTIVES/GOALS: The use of Human Centered Design (HCD) to improve the quality of team science is a recent application, and HCDs benefits and challenges have not been rigorously evaluated. We conducted a qualitative study with health sciences researchers trained in HCD methods to determine how they applied HCD methods and perceived its benefits and challenges. METHODS/STUDY POPULATION: The University of Pittsburgh offered HCD training to three cohorts of research scientists (staff as well as faculty) over a three-year period. The training was provided by the LUMA Institute, a premier HCD design firm with a highly regarded training program. We then evaluated this training by conducting 1-hour, semi-structured interviews with trainees from three training cohorts. Interviews focused on perceptions of the training, subsequent uses of HCD, barriers and facilitators, and perceptions of the utility of HCD to science teams. Data analysis was conducted using Braun and Clarkes process for thematic analysis. RESULTS/ANTICIPATED RESULTS: We interviewed 18 researchers (nine faculty and nine staff) trained in HCD methods and identified distinct themes regarding HCD use and its perceived benefits and challenges. Trainees found HCD relevant to research teams for stakeholder engagement, research design, project planning, meeting facilitation, and team management. They also described benefits of HCD in five distinct areas: creativity, egalitarianism, structure, efficiency, and visibility. We also identified challenges, including tensions between HCD approaches and academic culture. DISCUSSION/SIGNIFICANCE: Our data suggest that HCD has the potential to help researchers work more inclusively and collaboratively on interdisciplinary teams and generate more innovative and impactful science. The application of HCD methods is not without challenges; however, we believe these challenges can be overcome with institutional investment.